The Value of Freedom: A Review of the Current Developments and Conceptual Issues in the Measurement of Capability. Issue 3 (3rd July 2022) - Ubels, Jasper; Hernandez-Villafuerte, Karla; Schlander, Michael
ABSTRACT: In health economics, proponents of the capability approach argue that the value of health improvements should be evaluated us broad domains which reflect the capabilities of an individual. Instruments have been developed to measure these domains. These instruments operationalise the measurement of capability in different ways. The objective of this study is to analyze specifically how instruments operationalise the capability approach. Using a comprehensive pearl growing search methodology, we identified ten instruments. The content of these instruments was analysed in three stages. First, the definition of capability that was used for the development of an instrument was identified. Then, an analysis was conducted on how this definition was operationalised in the instrument's development. Lastly, the content of the instruments was compared with the concept "option freedom", which provides a more comprehensive definition of capability, to study whether the instruments measure capability or other aspects that are relevant for wellbeing assessment. We conclude that, despite using a shared definition of capability, the instruments differ in their methods to measure capability. Some instruments might miss content that reflect the burdens that people experience while achieving their capabilities in certain contexts. This might be due to the unclear conceptualisation of capability by Sen.